1994
DOI: 10.1111/j.1476-5381.1994.tb13080.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of contractile responses of rat small mesenteric arteries on nitric oxide and cyclo‐oxygenase and lipoxygenase products of arachidonic acid

Abstract: 1 We have examined the effects of nitric oxide inhibition, indomethacin and the dual lipoxygenase/ cyclo-oxygenase inhibitor, 3-amino-l-[m-(trifluoromethyl)-phenyl]-2-pyrazoline (BW755C), on the responses of small mesenteric arteries of Wistar rats, with and without endothelium, to noradrenaline, potassium chloride, endothelin-1, acetylcholine and sodium nitroprusside. 2 Noradrenaline, potassium chloride and endothelin-l caused concentration-dependent contraction of small mesenteric arteries. Indomethacin (14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
(47 reference statements)
2
12
3
Order By: Relevance
“…This difference in PE sensitivity was endothelium-dependent, since removal of endothelium abolished the difference. Endothelium-dependent a-adrenergic constriction in arteries can be modulated by the NO and cyclooxygenase pathways [39]. To investigate the mechanisms by which PE sensitivity was increased in parous rats, we blocked these pathways with l-NAME and meclofenamate respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in PE sensitivity was endothelium-dependent, since removal of endothelium abolished the difference. Endothelium-dependent a-adrenergic constriction in arteries can be modulated by the NO and cyclooxygenase pathways [39]. To investigate the mechanisms by which PE sensitivity was increased in parous rats, we blocked these pathways with l-NAME and meclofenamate respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins are one of those endothelial factors involved in vascular control, and we observed a diminished contraction to KCl in both groups pretreated with indomethacin. The effects of blockade of prostaglandins on MRA contractile responses appears to be dependent on the protocol used to test the responses; whereas an increased effect of indomethacin after a single dose of KCl was reported (41), a detailed study of the dependence of contractile responses of rat MRA on cyclooxygenase products indicated that indomethacin decreased contraction to a dose response curve of KCl (42). These effects appear to be mediated by cyclooxygenase as well as lipooxygenase vasoconstrictor products released during contraction to KCl (42).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of blockade of prostaglandins on MRA contractile responses appears to be dependent on the protocol used to test the responses; whereas an increased effect of indomethacin after a single dose of KCl was reported (41), a detailed study of the dependence of contractile responses of rat MRA on cyclooxygenase products indicated that indomethacin decreased contraction to a dose response curve of KCl (42). These effects appear to be mediated by cyclooxygenase as well as lipooxygenase vasoconstrictor products released during contraction to KCl (42). Our results suggest involvement of vasoconstrictor prostanoids in KCl contraction, in agreement with previous findings on the effects of prostanoids on adrenergic contraction in rat arteries (43;44).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, NO synthase inhibition causes a leftward shift in the concentration-response curve and an increased maximal response. 52 These effects are absent in the arteries investigated in this study, meaning that the NO production under basal conditions (for example, without agonist-induced stimulation) is blunted. None of the treatments could restore the L-NAME induced leftward shift and only hydralazine restored the increase in maximal contraction induced by L-NAME.…”
Section: Discussionmentioning
confidence: 65%
“…25,52 Again, this shift was completely absent in vehicle-, losartan-or hydralazine-treated groups. After 4 weeks of chronic dual NEP/ECE inhibition, however, L-NAME caused a significant leftward shift.…”
Section: Discussionmentioning
confidence: 94%